1998
DOI: 10.1021/jf970788d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model of the Cholesterol Oxidation during Heating

Abstract: The formation of cholesterol oxidation products (COPs) during heating of cholesterol at 150 °C for up to 30 min was kinetically studied using nonlinear regression models. The various COPs were analyzed by TLC and HPLC. Results showed that the COPs concentration increased with increasing heating time, and the cholesterol loss reached 64.8% after 30 min of heating. In the early stage of oxidation, the highest rate constant (h-1) was observed for 7-hydroperoxycholesterol (7-OOH) formation, followed by epoxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 32 publications
6
90
2
Order By: Relevance
“…A wide diversity of results has been noticed, even when comparing results from the same research group (15,27,28). Several studies performed sterol degradation at 150 °C using cholesterol samples.…”
Section: Effect Of Heating Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide diversity of results has been noticed, even when comparing results from the same research group (15,27,28). Several studies performed sterol degradation at 150 °C using cholesterol samples.…”
Section: Effect Of Heating Treatmentmentioning
confidence: 99%
“…Several authors have performed sterols kinetic studies (46), most of them using elegant approaches and complex mathematical calculations. Chien et al (27) found cholesterol degradation and oxysterols formation to follow first order and second order reactions and calculated the corresponding equations. Their work, as well as others, efficiently contributed to elucidate the mechanisms by which sterol oxidation occurs.…”
mentioning
confidence: 99%
“…Some authors pointed out that polymers and/or other products of relatively high molecular weight are also formed during sterol oxidation at high temperatures (Kim & Nawar, 1993;Chien, Wang & Chen, 1998;Soupas, Huikko, Lampi & Piironen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to regulate the formation of cholesterol oxidation products by means of radical inducers and radical scavengers [3,9,26,28]. These studies have mainly been done in solution.…”
Section: Cop Induction and Inhibitionmentioning
confidence: 99%
“…There was no obvious reason for these presumably short-lived open-shell cations to be present on the target. Cholesterol oxidation kinetics have been studied [9], and it is believed that any oxidation intermediates that correspond to radicals should have been transformed into the ultimate oxidation products rather rapidly.…”
Section: Introductionmentioning
confidence: 99%